Ethyl Glucuronide as a Long-term Alcohol Biomarker in Fingernail and Hair. Matrix Comparison and Evaluation of Gender Bias. (23rd February 2019) - Paul, R; Tsanaclis, L; Murray, C; Boroujerdi, R; Facer, L; Corbin, A
Abstract : Hair and fingernail samples were collected from 50 participants who provided details of their previous 90 days alcohol consumption. EtG concentration was measured in the samples using LC–MS-MS. Results showed significant correlation between alcohol consumption and EtG concentration in hair and fingernails. No gender bias was observed. Abstract: Aims: This work aimed to assess the performance of hair and fingernail ethyl glucuronide (EtG) measurement for use as a biomarker of alcohol consumption in persons with known drinking history across a range of drinking behaviours. Methods: EtG concentrations were assessed from the hair and fingernails of 50 study participants. Alcohol consumption of the previous 90 days was assessed by participant interview using the alcohol timeline follow-back method. EtG concentration was determined using LC–MS-MS using a method which was validated and accredited to ISO/IEC 17025 standards. Results: There was significant correlation between alcohol consumption and EtG concentrations found in hair and fingernail samples across the study group ( n = 50). From participants testing positive for EtG (male n = 14, female n = 13) no significant difference was found between male and female EtG levels in either hair or fingernails. Across all participants there was no significant difference in hair or fingernail EtG concentration between male ( n = 23) and females ( n = 27). Conclusions: Our results support the use of EtG to indicate alcohol consumption over the previous 90 days, or 3 months as is the normal practice in hair analysis. The results confirm that fingernails can be a useful alternative matrix where hair samples are not available.